Preparation and Characterization of Polyvinyl Alcohol-Nano Hidroxyapatite using Gamma Iradiation Technique for Biomaterial - Yessy Warastuti; Dian Pribadi Perkasa; Erizal Erizal; Basril Abbas; Sudirman Sudirman (Jurnal Keramik dan Gelas Indonesia, 2018)
ABSTRACTThe development and use of biomaterials in the biomedical field as bone implants are becoming increasingly important. Synthesis of polyvinyl alcohol (PVA) – bionanohydroxyapatite (HAp) composite hydrogel  has been carried using gamma irradiation technique. The PVA-HAp mixtures containing PVA (10-20%, w/v) and  a single concentration of HAp (20%w) were irradiated with various  irradiation doses  (0-20 kGy). The physico-chemical properties of irradiated composites were observed,includingmechanical properties, water absorption, biodegradation test, and characterized using Fourier-transform Infared Spectroscopy(FTIR), Transmission Electron Microscope (TEM)and Scanning Electron Microscopy (SEM). The results showed that the optimum  conditions wasPVA-HAp hydrogel composites (20%-20%, irradiation dose 20 kGy) with tensile strength 0.82 Mpa, elongation of 281.67%, water  absorption of 103.18%, and  biodegradation of 22.46%. The results of FTIR measurements of  PVA-HAp composites showed the occurrence of crosslinking  between PVA-HAp in the irradiation process. The SEM and TEM measurements showed that  HAp powder  was nano particle ( <60 mesh) and in the formed of fibers and with heterogen porousThe irradiated  PVA-HA composite  was expected to be  as candidate for  biomaterials application.